A training course on the employment of artificial intelligence (AI) to improve biomedical bibliographic searching: a report (Journal of EAHIL, 2025)
The article describes a training course conducted by GIDIF-RBM (Italian Association of Health Librarians) aimed at introducing biomedical documentation professionals to the use of generative artificial intelligence (AI) tools for enhancing bibliographic research. Held in October 2024, the course covered the practical application of AI-powered platforms such as ChatGPT, PubMed Buddy, Scispace, Rayyan, Dimensions, and others. Participants explored how these tools can improve the efficiency, relevance, and organization of literature searches. Pre- and post-course surveys assessed participants' familiarity with AI technologies and their emotional responses to their integration in professional routines. Results highlighted a mixture of curiosity, skepticism, and cautious optimism. While AI tools demonstrated value in supporting complex research tasks, outcomes varied across platforms, underlining the continued need for human critical thinking and contextual judgment. The initiative signals GIDIF-RBM's proactive role in preparing health information professionals for the opportunities and challenges posed by AI in biomedical knowledge management.